Analysis of the EGFR Amplification and CDKN2A Deletion Regulated Transcriptomic Signatures Reveals the Prognostic Significance of SPATS2L in Patients With Glioma - Wang, Haiwei; Wang, Xinrui; Xu, Liangpu; Zhang, Ji; Cao, Hua (Frontiers in Oncology, 2021)
Purpose: To analyze the prognostic effects of EGFR and CDKN2A alterations and determine the prognostic significance of EGFR and CDKN2A alterations regulated genes in patients with glioblastoma (GBM) or lower grade glioma (LGG). Methods: The alteration frequencies of EGFR and CDKN2A across 32 tumor types were derived from cbioportal based on The Cancer Genome Atlas (TCGA) datasets. The Kaplan-Meier analysis was used to determine the prognostic significance of EGFR and CDKN2A alterations. EGFR and CDKN2A alterations regulated expression signatures were identified from RNA-seq data in TCGA GBM datasets. The prognostic significance of EGFR and CDKN2A alterations regulated genes in patients with glioma were determined using TCGA and Chinese Glioma Genome Atlas (CGGA) datasets. Results: Compared with other 31 tumor types, EGFR amplification and CDKN2A deletion were particularly occurred in patients with GBM. GBM patients with EGFR amplification or CDKN2A deletion demonstrated poor prognosis. Statistic analysis showed the coexistence of EGFR alteration and CDKN2A deletion in GBM patients. We identified 864 genes which were commonly regulated by EGFR amplification and CDKN2A deletion and those genes were highly expressed in brain tissues and associated with cell cycle, EBRR2 and MAPK signaling pathways. SPATS2L was up regulated in GBM patients with EGFR amplification or CDKN2A alteration. Higher expression levels of SPATS2L were associated with worse prognosis in patients with GBM in both TCGA and CGGA datasets. Moreover, expression levels of SPATS2L were higher in patients with mesenchymal subtype of GBM. Statistic analysis also showed that the coexistence of EGFR alteration and CDKN2A deletion was significant in patients with LGG. SPATS2L was up regulated in LGG patients with EGFR amplification or CDKN2A alteration. Furthermore, higher expression levels of SPATS2L were associated with the worse prognosis in patients with LGG in both TCGA and CGGA datasets. Expression levels of SPATS2L were higher in patients with astrocytoma subtype of LGG. At last, the coexistence and unfavorable prognostic effects of EGFR amplification and CDKN2A alteration were validated using Memorial Sloan Kettering Cancer Center (MSKCC) glioma datasets. Conclusions: EGFR amplification and CDKN2A deletion regulated gene SPATS2L have significant prognostic effects in patients with GBM or LGG.